2001
DOI: 10.1002/ptr.705
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Streblus asper leaf extract

Abstract: Bactericidal activity was found in the 50% ethanol (v/v) extract of Streblus asper leaves. The extract possessed a selective bactericidal activity towards Streptococcus, especially to Streptococcus mutans which has been shown to be strongly associated with dental caries. The extract had no effect on cultures of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa, Staphylococcus coagulase positive, Staphylococcus coagulase negative, Serratia marcescens, Klebsiella pneumoniae, Enterobacter, Pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 7 publications
(4 reference statements)
0
35
0
Order By: Relevance
“…The MIC values for the volatile oil of Ixora Cocciniea were shown in table-2. Among the five burnt bacterial isolates, the MIC of volatile oil of Ixora Cocciniea observed at E.coli by the minimum zone of inhibition (Wongkham et al, 2001). …”
Section: Ecoli Proteus Vulgaris Kpneumonia Pseudomonas Aeruginosmentioning
confidence: 99%
“…The MIC values for the volatile oil of Ixora Cocciniea were shown in table-2. Among the five burnt bacterial isolates, the MIC of volatile oil of Ixora Cocciniea observed at E.coli by the minimum zone of inhibition (Wongkham et al, 2001). …”
Section: Ecoli Proteus Vulgaris Kpneumonia Pseudomonas Aeruginosmentioning
confidence: 99%
“…asper has been used in traditional medicine as decoction and pastes for wound infections. Several studies have reported that S. asper plant alcohol extract possess antibacterial and antiinflammatory activities (Wongkham et al, 2001) (Fig. 1).…”
Section: S Aspermentioning
confidence: 99%
“…1998;Nadkarni 2002). Scientific investigations have revealed various activities of S. asper such as anti-hepatitis B, analgesic, anticancer, anti-inflammatory, antioxidant and antimicrobial (Wongkham et al 2001;Phutdhawong et al 2004;Sripanidkulchai et al 2009;Basuri 2011;Chen et al 2012;Kumar et al 2012;Ibrahim et al 2013;Rao et al 2014). The literature also mentions that the stem bark of S. asper is a rich source of phyto-constituents, from which a number of compounds such as a-amyrin acetate, lupeol acetate, b-sitosterol, a-amyrin, lupeol and diol, strebloside and mansonin have been isolated (Prakesh et al 1992;Warrier 1996;Khare 2004;Rastogi et al 2006).…”
Section: Introductionmentioning
confidence: 99%